TIPE KEPRIBADIAN TOKOH UTAMA DALAM NOVEL “IMAJI DUA SISI” KARYA SAYFULLAN - Sari Tri Hastuti; Wachid Eko Purwanto (PIKTORIAL : Journal of Humanities, 2019)
This research is titled Personality Types of Main Characters in Novelof Two Sides of Sayfullan's Literature Psychology Study. The purpose of this research is to find out the personality type of the main character in Sayfullan's Two Sides novel. The subject of this research is Sayfullan's Two-Side Novel. The object of research study is the type of personality and main character. The research data collection method is reading notes. The research instrument is the data card. The research data analysis technique is descriptive qualitative. The results showed a dominant personality type, Melancholis. This research can be used as an alternative teaching material for Indonesian subjects in class XII high school based on curriculum 3013, revised 2018 through KD 3.8 and 4.8, namely interpreting the author's view of life in the novel that is read and analyzing the contents and presenting the results of the author's view interpretation. Keywords: Personality type, Sigmund Freud's psychoanalysis, Sayfullan's Two-Side Novel